2021
DOI: 10.3390/ijms222312981
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of SST4 Somatostatin Receptor Expression Using SST4-eGFP Knockin Mice and the Novel Rabbit Monoclonal Anti-Human SST4 Antibody 7H49L61

Abstract: Among the five somatostatin receptors (SST1–SST5), SST4 is the least characterized, which is in part due to the lack of specific monoclonal antibodies. We generated a knockin mouse model that expresses a carboxyl-terminal SST4-eGFP fusion protein. In addition, we extensively characterized the novel rabbit monoclonal anti-human SST4 antibody 7H49L61 using transfected cells and receptor-expressing tissues. 7H49L61 was then subjected to immunohistochemical staining of a series of formalin-fixed, paraffin-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A rabbit monoclonal antibody (7H49L61) that recognises the carboxyl-terminal tail of human SST4 was generated in collaboration with and obtained from Thermo Fisher Scientific (Waltham, MA, USA) and has been extensively characterised recently 35 . The peptide used to immunise rabbits was CQQEALQPEPGRKRIPLTRTTTF, corresponding to residues 366–388 of human SST4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rabbit monoclonal antibody (7H49L61) that recognises the carboxyl-terminal tail of human SST4 was generated in collaboration with and obtained from Thermo Fisher Scientific (Waltham, MA, USA) and has been extensively characterised recently 35 . The peptide used to immunise rabbits was CQQEALQPEPGRKRIPLTRTTTF, corresponding to residues 366–388 of human SST4.…”
Section: Methodsmentioning
confidence: 99%
“…We recently generated and thoroughly characterised a novel monoclonal anti-SST4 antibody, 7H49L61. We demonstrated that this antibody is well suited both for immunocytochemistry and immunoblot analysis in basic research and for immunohistochemical staining of formalin-fixed, paraffin-embedded routine pathology samples 35 .…”
Section: Introductionmentioning
confidence: 98%
“…The aim of the present study was to comprehensively re-evaluate SST and CXCR4 expression in a large set of thyroid carcinoma samples of all four entities by immunohistochemistry using well-characterised rabbit monoclonal antibodies. These monoclonal antibodies, which have several advantages over polyclonal ones, were previously generated and extensively characterised by our group [ 38 43 ] and have been validated by other researchers (e.g., [ 44 47 ]).…”
Section: Introductionmentioning
confidence: 99%